PENGARUH PEMBERIAN AIR REBUSAN AKAR DELIMA (PUNICA GRANATUM L.) TERHADAP MORTALITAS ASCARIS SUUM GOESZE. SECARA IN VITRO - SANDIKA, BAYU (Universitas Negeri Surabaya, 2012)
Pomegranate is one of plants that has a potential to treat askariasis because it contains high alkaloids and tannins, especially in the bark and roots. This study aims to prove the anthelmintic power of pomegranate root decoction water based on the rate of death or the mortality of A. suum Goesze. The research was carried out by soaking worms in the decoction water of pomegranate root which consists of four different concentrations, namely 0%, 21.56%, 43.12% and 64.68%. The research was conducted in three replications using a completely randomized design (CRD), then the data that was obtained is transformed using arcsin and analyzed by one-way ANAVA. From the research result, it can be concluded that the decoction water of pomegranate root affects to the mortality of A. suum Goesze. significantly after 48 hours exposure at a concentration of 64.68% and the characteristic of a dead worm is having a soft body and a transparent cuticle.